Modeling some properties of circadian rhythms - Miguel Lara-Aparicio; Carolina Barriga-Montoya; Pablo Padilla-Longoria; Beatriz Fuentes-Pardo (Mathematical Biosciences and Engineering)
Mathematical models have been very useful in biological research. From theinteraction of biology and mathematics, new problems have emerged that havegenerated advances in the theory, suggested further experimental work andmotivated plausible conjectures. From our perspective, it is absolutelynecessary to incorporate modeling tools in the study of circadian rhythmsand that without a solid mathematical framework a real understanding of themwill not be possible. Our interest is to study the main process underlyingthe synchronization in the pacemaker of a circadian system: thesemechanisms should be conserved in all living beings. Indeed, from anevolutionary perspective, it seems reasonable to assume that either theyhave a common origin or that they emerge from similar selectioncircumstances. We propose a general framework to understand the emergence ofsynchronization as a robust characteristic of some cooperative systems ofnon-linear coupled oscillators. In a first approximation to the problem wevary the topology of the network and the strength of the interactions amongoscillators. In order to study the emergent dynamics, we carried out somenumerical computations. The results are consistent with experiments reportedin the literature. Finally, we proposed a theoretical framework to study thephenomenon of synchronization in the context of circadian rhythms: thedissipative synchronization of nonautonomous dynamical systems.